2020
DOI: 10.1007/s40264-020-00942-3
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Adverse Event Recognition Systems in Twitter: Results from the Web-RADR Project

Abstract: Introduction A large number of studies on systems to detect and sometimes normalize adverse events (AEs) in social media have been published, but evidence of their practical utility is scarce. This raises the question of the transferability of such systems to new settings. Objectives The aims of this study were to develop an AE recognition system, prospectively evaluate its performance on an external benchmark dataset and identify potential factors influencing the transferability of AE recognition systems. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…To date, most of these studies processed data collected from Twitter [13][14][15][16][17][18][19][20][21][22]. Although social media platforms such as Twitter and Facebook are used in Russia, the most popular platforms are VK.com, which has about 97 million active monthly users [23], and Telegram Messenger, which is ranked second in the Russian Appstore, having 500 million active users overall.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, most of these studies processed data collected from Twitter [13][14][15][16][17][18][19][20][21][22]. Although social media platforms such as Twitter and Facebook are used in Russia, the most popular platforms are VK.com, which has about 97 million active monthly users [23], and Telegram Messenger, which is ranked second in the Russian Appstore, having 500 million active users overall.…”
Section: Introductionmentioning
confidence: 99%
“…Accounts of adverse reactions to drugs have been widely extracted from social media [11] in the context of mining consumer reviews on the Internet [12]. To date, most of these studies processed data collected from Twitter [1322]. Although social media platforms such as Twitter and Facebook are used in Russia, the most popular platforms are VK.com, which has about 97 million active monthly users [23], and Telegram Messenger, which is ranked second in the Russian Appstore, having 500 million active users overall.…”
Section: Introductionmentioning
confidence: 99%
“…7 The potential for analysing and managing this incessant flow of information lies in the development of artificial intelligence (AI) systems, which will help not only the identification of reports but also the control of their quality and their follow-up. 8 10 Projects in this direction are being set up 11 , 12 , 19 , 20 and are hampered by costs, by technical difficulties 21 and probably by the lack of clear regulatory guidance for the digital and social media area. Pharmacovigilance legislation, and regulations concerning other healthcare products, such as medical device, appears to be lagging behind the rapid development of the sector.…”
Section: Introductionmentioning
confidence: 99%
“…To expand the scope of pharmacovigilance to patients' viewpoints, it is necessary to include data sources that can be used to analyze patient situations. Several studies [4][5][6] have explored the use of web-based resources such as Twitter in pharmacovigilance to include patients' viewpoints. Similarly, in Japan, we previously examined Japanese-language disease blogs (tōbyōki) as a resource for patient-generated data from the internet to augment pharmacovigilance [7].…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies [ 4 , 8 ] have reported the utility of patient-derived data from the web for pharmacovigilance, concern over the effect of irrelevant data (ie, noise) has led some researchers to recommend that these data alone should not be used to derive pharmacovigilance statistics [ 9 ]. Using data from additional sources is one way to minimize this effect.…”
Section: Introductionmentioning
confidence: 99%